Inframesocolic approach to the duodenal papilla - Delgado, Bolivar; Puig, Roberto; Liard, Washington; Cardoso, Tabaré; Voelker, Ricardo (Cirugía del Uruguay, 1975)
The transduodenal inframesocolic approach of the papilla is an excellent procedure to act upon it, on reoperations due to residual pathology or even on the first operation. The authors describe the anatomical basis of the procedure: they insist upon the frequent low location of the papilla in the second duodenal portion, and upon its anterior relations with the right mesocolon -attached to the mesoduodenum- and its contents, the pedicles of the right colic angle, which generally leave an avascular preduodenal area which enables the entering. They analyze its advantages, specially in the presence of adherences due to previous operations upon the biliary tract, and its disadvantages, limited to the unusually high locations of the papilla and to the obesity of the patient, with fatty mesos, where vascular elements are difficult to identify. The authors analyze the technique of the procedure in detail, and they report 2 observations in which it was used with excellent results.